Analisis LQ dan Shift Share Kabupaten Bandung Barat - Eka Purna Yudha; Nurhazna Fairuz Ardiani (Universitas Galuh, 2026)
This study aims to analyze the structure and performance of the West Bandung Regency economy based on leading sectors and sectoral competitiveness. The methods used are Location Quotient (LQ) and Shift Share with Gross Regional Domestic Product (GRDP) data for the 2016–2024 period. LQ analysis is used to identify base sectors, while Shift Share is used to assess the influence of national growth, industrial structure, and regional competitive advantage. The analysis results show that base sectors in West Bandung Regency include Accommodation and Food and Beverage Provision, Real Estate, Electricity and Gas Procurement, Agriculture, Forestry and Fisheries, Educational Services, Corporate Services, and Government Administration. The Accommodation and Food and Beverage Provision sector is the most dominant sector with the highest LQ value. Shift Share analysis shows that regional economic growth is strongly influenced by national economic dynamics, especially in the manufacturing and trade sectors. Although some sectors show increased competitiveness post-pandemic, the regional economic structure remains relatively dependent on the service and natural resource sectors with a limited level of diversification. Therefore, a development strategy is needed that encourages the strengthening of non-basic sectors and increases the competitiveness of the modern services sector to support more sustainable regional economic growth.